Health Perception and Participation in Daily Activities during the Menstrual Period among Secondary School Girls in Nepal - Khadka, Kalpana; Chaudhary, Dhanaraj; Koirala, Sharmila (International Research Journal of MMC, 2025)
This paper explored the menstruation experience, confidence, and hygiene behaviors, and activities of secondary schoolgirls in Nepal, using average scores and independent t-tests to compare girls attending public and private schools. Most of the psychosocial and behavioral measures evidenced clear differences between the two groups. Private-school students reported a bigger drop in confidence during their periods (p = .018) and felt more uneasy about joining social events (p = .000), which suggests stronger social or peer pressures. In contrast, public-school girls felt more uncomfortable with participating in school activities, which may reflect ongoing limitations in infrastructure and support at public schools (p = .021). Hygiene practices were reportedly quite good across both groups, as evidenced by frequent carrying of sanitary pads, frequent changes of sanitary pads, and washing with soap and water, though private-school students were more consistently carrying sanitary pads outside the home (p = .033). Most of the cultural practices, such as sleeping on temporary beds, did not differ meaningfully between school types. One final exception was nutrition: public-school students were much more likely to report eating a balanced diet during menstruation (p = .000), reflecting variations in dietary norms or family expectations. Overall, the findings indicate that while hygiene has improved across both settings, confidence, participation, and some of the cultural restrictions persist according to the socio-educational context. The paper highlights the need for school-tailored interventions addressing psychosocial barriers, the creation of more menstruation-friendly environments, and supportive norms within both the public and private education systems.